Waiting time for pediatric patients to be admitted for elective surgery at a National Pediatric Health Institute in Mexico City - Edmundo Vázquez-Cornejo; Elizabeth Cruz-Cruz; Heriberto Gómez-Gaytán; César M. Zambrano-Virgen; Miriam G. Herrera-Segura; Araceli Saldívar-Flores; Olga Morales-Ríos; Juan Garduño-Espinosa (Boletín Médico del Hospital Infantil de México)
Background: Waiting times for elective surgery can be a physically and psychologically distressing experience for patients, affecting their satisfaction and perceptions of service quality. This study aimed to estimate the waiting time for pediatric patients admitted for elective surgery, identify events causing delays, and compare variations in the admission process. Method: Three cohorts of pediatric patients scheduled for elective surgery were prospectively followed: (A) weekday general surgery admissions, (B) weekday admissions to other surgical specialties, and (C) weekend surgical admissions. The admission process was mapped, timescales of each stage were recorded, and delay incidents were identified through direct non-participant observation after obtaining informed consent or assent. Results: The mean waiting time was 6.9 h (95% confidence interval [CI]: 6.6-7.2 h) for all scheduled surgical admissions. Patients in cohort B experienced the longest waiting time at 8.1 h (95% CI: 7.7-8.5 h, p < 0.0001). Primary causes of delay included lengthy transfers to the admission area, bed management issues, and limited staff availability during shift changes. Avoidable delays resulted in a mean additional waiting time of 1.4 h. Conclusions: The findings suggest that hospital waiting times could be reduced through organizational interventions targeting the main causes of delay and simplifying administrative processes.